Protection from Amyloid β Peptide–Induced Memory, Biochemical, and Morphological Deficits by a Phosphodiesterase-4D Allosteric Inhibitor - Cui, Su-Ying; Yang, Ming-Xin; Zhang, Yong-He; Zheng, Victor; Zhang, Han-Ting; Gurney, Mark E.; Xu, Ying; O’Donnell, James M. (The Journal of pharmacology and experimental therapeutics, 2019)
Recent imaging studies of amyloid and tau in cognitively normal elderly subjects imply that Alzheimer’s pathology can be tolerated by the brain to some extent due to compensatory mechanisms operating at the cellular and synaptic levels. The present study investigated the effects of an allosteric inhibitor of phosphodiesterase-4D (PDE4D), known as BPN14770 (2-(4-((2-(3-Chlorophenyl)-6-(trifluoromethyl)pyridin-4-yl)methyl)phenyl)acetic Acid), on impairment of memory, dendritic structure, and synaptic proteins induced by bilateral microinjection of oligomeric amyloid beta (Aβ1–42 into the hippocampus of humanized PDE4D (hPDE4D) mice. The hPDE4D mice provide a unique and powerful genetic tool for assessing PDE4D target engagement. Behavioral studies showed that treatment with BPN14770 significantly improved memory acquisition and retrieval in the Morris water maze test and the percentage of alternations in the Y-maze test in the model of Aβ impairment. Microinjection of oligomeric Aβ1–42 caused decreases in the number of dendrites, dendritic length, and spine density of pyramid neurons in the hippocampus. These changes were prevented by BPN14770 in a dose-dependent manner. Furthermore, molecular studies showed that BPN14770 prevented Aβ-induced decreases in synaptophysin, postsynaptic density protein 95, phosphorylated cAMP-response element binding protein (CREB)/CREB, brain-derived neurotrophic factor, and nerve growth factor inducible protein levels in the hippocampus. The protective effects of BPN14770 against Aβ-induced memory deficits, synaptic damage, and the alteration in the cAMP-meditated cell signaling cascade were blocked by H-89 (N-[2-(p-Bromocinnamylamino)ethyl]-5-isoquinolinesulfonamide dihydrochloride), an inhibitor of protein kinase A. These results suggest that BPN14770 may activate compensatory mechanisms that support synaptic health even with the onset of amyloid pathology in Alzheimer’s disease. This study demonstrates that a phosphodiesterase-4D allosteric inhibitor, BPN14770, protects against memory loss and neuronal atrophy induced by oligomeric Aβ1–42. The study provides useful insight into the potential role of compensatory mechanisms in Alzheimer’s disease in a model of oligomeric Aβ1–42 neurotoxicity.